HUBUNGAN LAMA POSISI DUDUK SAAT BEKERJA DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEKERJA DI HOME INDUSTRI VANNY PIGORA DESA KURIPANSARI PACET MOJOKERTO - Triwibowo, Heri; Rachma Dewi, Indah (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The low back pain is a painful syndrome which happens in low back part; it is called work related musculoskeletal disorders. It may happen because of either muscle tense or inappropriate body’s structure as well as the long duration of sitting.Sit duration is time working with sit position within a day. The employees of Vanny Pigora Industry work while sitting, so that it takes a risk on back pain. In this case, this study aimed at investigating the correlation of duration of sit working position with the complaint of the low back pain toward Vanny Pigora Home Industry’s employees in Kuripansari Village Pacet Mojokerto.This study used correctional analytic research design. The independent variable was the duration of sit position and the dependent variable was the complaint of low back pain. The number of population were the whole employees in home industry. The number of sample were 30 respondents in which taken by Non Probability Sampling with total sampling technique. The data were collected by using observation and interview technique. The data which were obtained with cross tabulation indicated the result of sit duration around >4 hours toward 16 persons (53, 3%), 4 persons (13, 3%) did not get the low back pain, 7 persons (23, 3%) got minor scale, 4 persons (13, 3%) got medium scale, and 1 person (3, 3%) got serious scale. The findings revealed that there were a correlation of sit position with the complaint of low back pain. The respondents need to gain information about how to prevent the low back pain with ergonomic sit position and enough break time while working.Key words: Sit Duration, The Low Back Pain